Maternal serum C - reactive protein and fibrinogen concentration in women with pre-eclampsia - Mohammad Abedi Samakoosh; Shahla Yazdani; Zinatosadat Bouzari; Masoumeh Golsorkhtabaramiri (Babol University of Medical Sciences, 2015)
Background: Despite many studies published in recent years concerning pathogenic mechanisms of pre-eclampsia, but this issue remains controversial. The aim of the present study was to compare C-reactive protein (CRP) level and fibrinogen concentration obtained from pregnant women with pre-eclampsia with those obtained from women with normal pregnancies.  Methods: In a case-control study, 40 pregnant women with mild pre-eclampsia were studied. The maternal serum CRP and fibrinogen concentration of the 40 patients were compared with 55 pregnant women with non-preeclampsia as a control group. CRP was examined using quantitive nephlometry and fibrinogen concentration was measured by clotting system. An independent sample t-test was used for analysis.  Results: Maternal serum CRP was higher in women pregnant with pre-eclampsia compared with those from pregnant women normal pregnancies (p= 0.01). The independent t-test did not reveal any statistically significant differences in the fibrinogen concentration between these pregnant women, either with or without pre-eclampsia.  Conclusion: The findings of this study indicated that a novel increased CRP was identified among pregnant women with pre-eclampsia, making inflammatory marker as a promising new approach for the detection of pre-eclampsia.